A putative monofunctional glycosyltransferase is expressed in Ralstonia eutropha. - Paik, J (1997)
A gene, mgt, encoding a protein homologous to the N-terminal module of class A high-molecular-mass penicillin-binding proteins was identified in Ralstonia eutropha. By using specific antibodies, the corresponding Mgt protein was detected in association with the membrane, confirming that the N-terminal hydrophobic segment functioned as a membrane anchor. A derivative in which the hydrophobic sequence was deleted was overexpressed as a maltose-binding fusion protein in Escherichia coli. Cleavage of the product resulted in substantial amounts of soluble Mgt derivative, indicating that folding occurs independently on other proteins or on homologous domains of penicillin-binding proteins.